Pengaruh Harga Transfer Terhadap Agresivitas Pajak pada Perusahaan Manufaktur dan Pertambangan di Indonesia - Nur Alfiah Rezkiyanti; Emayanti Christina Hutabara (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to analyze the influence of transfer pricing on tax aggressiveness in manufacturing and mining companies listed in Indonesia. The specific objective is to determine whether transfer pricing practices affect the company's level of effort in reducing its tax burden.. Method: Quantitative approach, using secondary data in the form of financial statements from manufacturing and mining companies. The analysis technique used is simple linear regression to test the effect of transfer pricing variables on tax aggressiveness. Finding: The research results indicate that transfer pricing significantly affects tax aggressiveness. Companies engaging in transfer pricing practices tend to have higher levels of tax aggressiveness. This suggests that transfer pricing is one of the company's strategies for minimizing tax burdens. Novelty: The research focuses on two sectors simultaneously (manufacturing and mining), which are rarely analyzed together in relation to transfer pricing.